Becoming a World-Class University The case of King Abdulaziz University - Tayeb, Osama; Zahed, Adnan; Ritzen, Jozef (Springer International Publishing : Imprint: Springer, 2016)
This book written by international experts in the field of educational innovation is a guide for universities to become world-class universities. It contributes to the current international intellectual debate on the future of higher education. It also tells the story of King Abdulaziz University in Jeddah (Saudi Arabia) and its effort to become a world-class university. The book discusses excellence in different aspects such as education, research, community services, strategic planning, knowledge economy and international cooperation.